Fast assembly of MXene hydrogels by interfacial electrostatic interaction for supercapacitors. Issue 82 (29th September 2021) - Peng, Mengke; Yang, Weizu; Li, Longbin; Zhang, Kaiyang; Wang, Li; Hu, Ting; Yuan, Kai; Chen, Yiwang
Abstract : A 3D MH/Th hydrogel was rapidly assembled via electrostatic interaction and such a structure could effectively suppress restacking and oxidation, and enlarged the surface utilization of the MXene for supercapacitors. Abstract : A simple and fast method for preparing MXene hydrogels is proposed by introducing protonated thionine molecules into a MXene dispersion through electrostatic interaction. Such a 3D hydrogel effectively suppressed restacking and oxidation, and enlarged the surface utilization of the MXene, producing an improved specific capacitance of 163 F g −1 at 1 A g −1 and excellent stability when used as an electrode material for supercapacitors.